HUBUNGAN ANTARA PEMAHAMAN KONSEP SEJARAH DENGAN PEMBENTUKAN IDENTITAS NASIONAL SISWA SEKOLAH DASAR - Mas'ad, Mas'ad; Arif, Arif; Syafril, Syafril; Munandar, Anas (Universitas Muhammadiyah Mataram, 2024)
This study aims to analyze the relationship between understanding the concept of history and the formation of national identity of elementary school students through a literature study approach. History as a subject that teaches about important events in the journey of a nation has a strategic role in building national awareness and national identity. A good understanding of history can strengthen pride and loyalty to the country, and help students understand the basic values that shape the character of the nation. In this study, data were collected through a literature review covering various sources, such as history textbooks, scientific journals, and previous research relevant to this topic. The results of the literature study indicate that a good understanding of history can strengthen students' national identity, especially in terms of recognizing state symbols, the struggle for independence, and the diversity of Indonesian culture. A number of theories in educational science also underline the importance of contextual history learning based on national values to form a sense of unity. In addition, interesting and interactive history learning can increase student involvement, thereby helping to form a stronger national identity. This study suggests that history education in elementary schools emphasizes learning that is not only factual, but also leads to strengthening national values that are relevant to students' daily lives.